Implementasi Nilai Karakter dalam Pembelajaran Proses Pemesinan Komplek Menggunakan Metode Pembelajaran Kolaboratif - Paryanto Paryanto (Jurnal Pendidikan Teknologi dan Kejuruan, 2014)
The objectives of this study were (1) to analysethe changes of the students’ attitudes resulted by the implementation of characters education in the practice of Complex Machining Processes using the collaborative skills based method; (2) to assess the improvement of the students’ achievement after the implementation. This study is a Class Action Research conducted in the practice of Complex MachiningProcesses. The data collection  was conducted using observation, documentation, interviews and assessment results of the practices. The data analysis technique useda quantitative descriptive analysis. The results revealed: (1) the significant positive attitudinal changesof the students with the averages of 30% ; (2) the students increased the achievement with the averages of 7 points.